ANALISIS PEMBINAAN PRESTASI PEMUDA TERHADAP AKTIVITAS PENCAK SILAT PSHT DI KABUPATEN BANYUWANGI - Ajeng Yulin Kusuma (Fakultas Ilmu Sosial dan Ilmu Politik Universitas 17 Agustus 1945 Banyuwangi, 2021)
Abstrac: Analist For Fostering Youth Achievements in Martial Arts Activities in Banyuwangi Distric Martial arts is an ancestral cultural heritage that must be preserved and preserved. There are various kinds of martial arts colleges in Banyuwangi, one of which is PSHT. Ther is also the purpose of martial arts PSHT, which is to educate virtuous people to know right and wrong and devote to God Almighty, which means that besides teaching about martials arts, PSHT also teaches about moral education. This is very necessary as a moral formation for young people. But along with the development of the times there are some young people who do negative actions that can harm themselves and others and the surrounding environment such actions are commonly reffered to as youth paathology. Therefore ways to prevent the occurence of youth pathology can be directed to follow the PSHT martial arts. Because martial arts has been consideret good, the government supports these activities by making martial arts as one of the sports contested. So that the government held an event with a target specifically for youth. The objective to be achieved are to print superior, productive, and accomplished youth.